2016
DOI: 10.4049/jimmunol.1600611
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Precedes IL-5 in Regulating Eosinophil Commitment and Is Required for Eosinophil Homeostasis

Abstract: Eosinophils are important in the pathogenesis of many diseases, including asthma, eosinophilic esophagitis, and eczema. While IL-5 is crucial for supporting mature eosinophils, the signals that support earlier eosinophil lineage events are less defined. The IL-33 receptor, ST2, is expressed on several inflammatory cells, including eosinophils, and is best characterized for its role during the initiation of allergic responses in peripheral tissues. Recently, ST2 expression was described on hematopoietic progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 45 publications
10
109
1
Order By: Relevance
“…Further, it is well established that the IL-33 receptor (ST2) is expressed on a variety of type 2 cytokine-related HSPCs including eosinophil, basophil and mast cell progenitors suggesting IL-33 may also be capable of promoting progenitor cell responses. This is supported by recent work demonstrating that IL-33 plays a critical role in regulating murine eosinophil hematopoiesis (162). Supporting these murine studies, elevated CD34 + progenitor cell populations have been identified in the inflamed tissues of patients suffering from nasal polyposis and asthma (162, 163).…”
Section: Innate Immunitysupporting
confidence: 63%
See 1 more Smart Citation
“…Further, it is well established that the IL-33 receptor (ST2) is expressed on a variety of type 2 cytokine-related HSPCs including eosinophil, basophil and mast cell progenitors suggesting IL-33 may also be capable of promoting progenitor cell responses. This is supported by recent work demonstrating that IL-33 plays a critical role in regulating murine eosinophil hematopoiesis (162). Supporting these murine studies, elevated CD34 + progenitor cell populations have been identified in the inflamed tissues of patients suffering from nasal polyposis and asthma (162, 163).…”
Section: Innate Immunitysupporting
confidence: 63%
“…This is supported by recent work demonstrating that IL-33 plays a critical role in regulating murine eosinophil hematopoiesis (162). Supporting these murine studies, elevated CD34 + progenitor cell populations have been identified in the inflamed tissues of patients suffering from nasal polyposis and asthma (162, 163). Collectively, these studies suggest that cytokine alarmins not only recruit HSPCs to peripheral tissues but also alter their functional properties, enabling them to selectively promote type 2 responses (Fig.…”
Section: Innate Immunitysupporting
confidence: 63%
“…Importantly, although EoP stains with eosin, eosin-negative precursors have been reported (42), suggesting a precursor stage prior to the granulation events occurring in EoP. We identified an EoPre that is eosin negative and exhibits the characteristic donut-shaped nuclei, which is driven by IL-33 exposure (44) (Figure 1A). Both EoP and EoPre are IL-5Rα + , but EoPre is Siglec-F lo SSC lo whereas EoP is Siglec-F + SSC hi .…”
Section: The Effects Of Il-33 On Mature and Developing Eosinophilsmentioning
confidence: 77%
“…IL1RAP is co-receptor with IL1R1 for IL1 and with IL1RL1 for IL-33 signaling. The receptor for IL-33, IL1RL1/IL1RAP is expressed on mature blood and airway EOS, and EOS progenitors (2931) . IL-33 activates EOS to release cytokines such as GM-CSF, which increases their survival in an autocrine manner (32, 33) .…”
Section: Resultsmentioning
confidence: 99%